The Mission of the Triune God Trinitarian Missiology in the Tradition of Lesslie Newbigin. - Dodds, Adam.; Rae, Murray (Eugene : Wipf and Stock Publishers, 2017)
Lesslie Newbigin was arguably the greatest missionary thinker of the twentieth century. After a successful missionary career in south India, Newbigin pioneered missionary engagement with the secular West and resurgent Islam. He also led the way in arguing that the Church's mission can only be understood in light of the doctrine of the Trinity. Over fifty years ago, Newbigin called for the further development of missionary thinking grounded in the Triune being of God. This work is in response to that call. Adam Dodds provides the first in-depth study of Newbigin's trinitarian theology of missio.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 250; Pages:251 to 275; Pages:276 to 300; Pages:301 to 325; Pages:326 to 350; Pages:351 to 354
Description based upon print version of record.
Includes bibliographical references and index.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 600, 650
Keywords: Newbigin, Lesslie; Missions -- Theory; Trinity; RELIGION / Christianity / Methodist; Electronic books